AMBIGUITAS DAN DAMPAK NEGATIF PEMILIHAN KEPALA DAERAH LANGSUNG DALAM PERSPEKTIF FILOSOFI PANCASILA - Ridhuan, Syamsu; Ningsih, Rahmah; Nur, Syurya Muhammad (Universitas Esa Unggul, 2021)
There is no relevance of the direct regional head election system to democracy in the perspective of the Pancasila philosophy. This is the conclusion of the study, measuring the level of relevance of the direct election system for regional heads with democracy in the perspective of the Pancasila philosophy. A reflection of Pancasila education learning in universities. The study analyzed as many as 763 students as respondents who were taking Pancasila Education courses. Analysis of the research ambiguity occurs, the implementation of the regional head election directly received the support of the wider community. However, the philosophy of Pancasila is not inherent in the existence of the essence of the values and norms of Pancasila, the fourth principle of Pancasila